Public Accountability in Non-Profit Organizations in Kampung Tridi Malang - Besin, Egidio Da Neves Brito; Sopanah, Ana; Hasan, Khojanah (Mahameru Publisher, 2023)
This writing aims to find out how public accountability is for non-profit organizations in Tridi Village, Malang City. This study uses qualitative methods with descriptive analysis. The results of the research show that Kampung Tridi has implemented the principle of accountability starting from the planning, implementation, and accountability processes quite well. Where, in the plan, Tridi village administrators hold regular meetings to discuss the work program to be held and also the budget. Meanwhile, in the process of implementing it, Tridi village administrators kept records regarding income and expenses in Tridi village and in the implementation of the work program all residents participated, this indicates residents' awareness of accountability and transparency in financial management in Tridi Malang village. Next, in the process of accountability the management of Tridi village reports regularly to the residents on the financial reports that have been recorded, this indicates that there is openness to the residents so that the community's trust in the management of Tridi village is getting higher. However, related to the financial reports that are made are still very simple, because they only record income and expenses, they are not guided by the standards that apply to non-profit organizations today, namely ISAK 35.